Characterization of the Goose CAPN3 Gene and its Expression Pattern in Muscle Tissues of Sichuan White Geese at Different Growth Stages - Hengyong Xu; Yahui Zhang; Quan Zou; Liang Li; Chunchun Han; Hehe Liu; Jiwei Hu; Tao Zhong; Yan Wang (The Journal of Poultry Science, 2018)
Calpain 3 (CAPN3), also known as p94, is associated with multiple production traits in domestic animals. However, the molecular characteristics of the CAPN3 gene and its expression profile in goose tissues have not been reported. In this study, CAPN3 cDNA of the Sichuan white goose was cloned, sequenced, and characterized. The CAPN3 full-length cDNA sequence consists of a 2,316-bp coding sequence (CDS) that encodes 771 amino acids with a molecular mass of 89,019 kDa. The protein was predicted to have no signal peptide, but several N-glycosylation, O-glycosylation, and phosphorylation sites. The secondary structure of CAPN3 was predicted to be 38.65% α-helical. Sequence alignment showed that CAPN3 of Sichuan white goose shared more than 90% amino acid sequence similarity with those of Japanese quail, turkey, helmeted guineafowl, duck, pigeon, and chicken. Phylogenetic tree analysis showed that goose CAPN3 has a close genetic relationship and small evolutionary distance with those of the birds. qRT-PCR analysis showed that in 15-day-old animals, the expression level of CAPN3 was significantly higher in breast muscle than in thigh tissues. These results serve as a foundation for further investigations of the function of the goose CAPN3 gene.